Layer-by-layer assembly of ordinary and composite coordination multilayers - Doron-Mor, Ilanit (Langmuir : the ACS journal of surfaces and colloids, 2004)
Coordination self-assembly of bishydroxamate-based metal-organic multilayers on gold employing a layer-by-layer (LbL) approach was investigated. It is shown that the solution chemistry of the participating metal ion has a marked influence on the composition and properties of the multilayers. Use of Ce4+ and particularly zirconium(IV) acetylacetonate (Zr(acac)4) solutions in the ion-binding step of multilayer construction leads to multilayers with a near-stoichiometric metal ion-to-ligand ratio, suggesting a structure close to that predicted by a simple coordination self-assembly scheme. On the other hand use of a ZrCl4 solution as the source of metal ions in the multilayer construction leads to a multilayer with greater thickness and a large excess of Zr(IV), evenly distributed between the organic layers. In the latter case, a ratio of ca. 1:2 between the excess Zr and oxygen, as well as long-term Zr4+ binding experiments showing deposition of ZrO2, suggest the formation of a zirconia-type nanophase between the bishydroxamate organic repeat units during multilayer self-assembly. Hence, while the multilayer prepared using Zr(acac)4 solution appears to represent a "true" coordination-based structure, the one prepared using ZrCl4 is best described as a composite organic-ceramic multilayer. Composite multilayers prepared in this way display different properties from those of the stoichiometric ones, such as improved dielectric behavior and higher stiffness. Even greater mechanical stability is obtained with multilayers constructed using alternate binding of ZrCl4 and Ce4+. The concept of LbL formation of coordination-based composite organic-ceramic structures may be useful in obtaining nanometer-scale structures with tunable properties